Thin films of topological crystalline insulator SnTe in contact with heterogeneous atomic layers - Chi-Hsuan Lee; Chih-Kai Yang (New Journal of Physics, 2016)
Tin telluride is a topological crystalline insulator that has gapless surface states protected by mirror symmetry. The symmetry remains intact when the insulator is reduced in thickness and becomes a thin film, according to ab initio calculations based on density functional theory. Furthermore, a SnTe thin film in contact with a heterogeneous atomic layer is capable of closing energy gap caused by quantum tunneling between the two thin film surfaces and therefore distinguishes two conducting channels through surface and interface states respectively. Our calculations of SnTe films deposited with a lead telluride layer have two Dirac cones separated in energy, while the same film in contact with strontium telluride have the cones separated in momentum. The composite with a magnetic manganese telluride layer, however, loses both the mirror and time-reversal symmetry.